Synthesis of silver nanoparticles using a Mentha spicata extract and evaluation of its anticancer and cytotoxic activity - Torres Martínez, Yuridia; Arredondo Espinoza, Eder Ubaldo; Puente, Carlos; González Santiago, Omar; Pineda Aguilar, Nayely; Balderas Rentería, Isaías; López, Israel; Ramírez Cabrera, Mónica Azucena (PeerJ Inc., 2019)
In this study, silver nanoparticles (NP) were synthesized by two methods: using an aqueous extract of Mentha spicata leaves and using citrate ions as stabilizing agent, and the cytotoxicity and anticancer activity of both NP were evaluated in vitro. The particles synthesized with the aqueous extract were spherical with a size ranging from 15 to 45 nm. These NP decreased cell viability in all of the cells studied; however, the IC50 could only be estimated in the Chang liver cells (IC50 = 21.37 µg/mL). These particles also decreased the generation of reactive oxygen species in Chang and SiHa cells. Additionally, the dispersions decreased the activity of caspase-3. There was no significant difference between the biological activities of the NP obtained with the aqueous extract and the NP synthesized using citrate ions. This study showed that an aqueous extract of M. spicata is an excellent alternative for the synthesis of silver NP. These NP showed cytotoxicity and anticancer activity in vitro. Although more experiments are required, the cell death occurs probably through a mechanism different from apoptosis.